2014
DOI: 10.1111/geb.12234
|View full text |Cite
|
Sign up to set email alerts
|

Will among‐population variation in seed traits improve the chance of species persistence under climate change?

Abstract: Aim Seed traits related to recruitment have direct relevance for plant fitness and persistence. Trait variation in time and among populations may increase species resilience and ultimately reduce the risk of extinction. However, patterns of amongpopulation variation in critical recruitment traits remain poorly known and are often disregarded when considering extinction risk under future climates.Location Global. MethodsIn this paper we review and synthesize current knowledge about among-population variation in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
197
2
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(211 citation statements)
references
References 131 publications
(181 reference statements)
6
197
2
6
Order By: Relevance
“…Furthermore, some studies have suggested that PY variability allows seeds to persist in variable environments (Ooi et al 2012;Fernández-Pascual et al 2013). However, there is scarce knowledge about the degree of PY variability, both among and within populations, especially in natural ecosystems (Cochrane et al 2015;Hudson et al 2015).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, some studies have suggested that PY variability allows seeds to persist in variable environments (Ooi et al 2012;Fernández-Pascual et al 2013). However, there is scarce knowledge about the degree of PY variability, both among and within populations, especially in natural ecosystems (Cochrane et al 2015;Hudson et al 2015).…”
mentioning
confidence: 99%
“…Moreover, most studies focused on PY variation among populations and individuals were performed in agricultural species, mainly in annuals and short-lived herbaceous perennials, but very few have dealt with woody species (Cochrane et al 2015;Hudson et al 2015). Vachellia aroma (Gillies ex Hook.…”
mentioning
confidence: 99%
“…Seeds are inherently plastic, with complexity of function apparent at any level (e.g. within and between species, plant populations, individual plants and seed populations) (Cochrane et al 2015b). Dormancy is a predominant trait in many floras, and complex dormancy is common in the Australian flora (Merritt et al 2007).…”
Section: Emerging Themes and Future Directionsmentioning
confidence: 99%
“…The suitable environment allows the persistence of those adapted species to germinate, grow, and reproduce, thus maintaining species abundance. However, this adaptation has been undergoing a rapid transformation in recent years, predominantly due to the effects of global warming bringing significant changes to climatic conditions [6,7]. It has been estimated that the earth's surface temperature has risen by 0.6 ∘ C over the past 100 years and the projections for future warming suggested an alarming 2 ∘ C in this century [8,9].…”
Section: Introductionmentioning
confidence: 99%